Real-Time Temperature Monitoring VHMS Dashboard Development to Reduce Component Unscheduled Breakdown - Nur, M. Hidayatullah; Hendriana, Dena; Baskoro, Gembong (BIP's JURNAL BISNIS PERSPEKTIF, 2025)
The coal mining industry relies on heavy equipment such as excavators and bulldozers and their efficiencies are critical for the productivity. This paper addresses the issue of unscheduled breakdowns due to high operational temperatures which impacts productivity, equipment availability and maintenance costs. The existing Vehicle Health Monitoring System (VHMS) from Komatsu Original Manufacturing lacks of real-time data for coolant temperature. The data recording is only every 20 hours and data reporting to the monitoring system is transferred daily. This lack of data is leading to unable for identifying the causes of problems. This study proposes a real-time temperature monitoring dashboard for the VHMS to track and manage Komatsu equipment temperature limits and to upgrade the existing system to record temperature data in every second instead of every 20 hours. This fine data collection provides enough information for a comprehensive analysis of machine conditions. This allows for quick identification of abnormal temperature trends, leading to timely maintenance and failures prevention. The new dashboard system provides immediate access to detailed temperature data, facilitating prompt decision-making in maintenance process. It also involves setting new temperature limits to prevent overheating and reduce unscheduled component breakdown from 25% in 2019 to 0% in 2023 and 2024. Implementing a real-time temperature monitoring dashboard is expected to improve equipment availability, reduce breakdowns, optimize maintenance schedules and lower operational costs in the coal mining industry.